Research on task offloading algorithm of mobile edge computing based on deep reinforcement learning in SDCN - Shouhua JIANG; Yiwu WANG (Dianxin kexue)
With the continuous development of network technology, the network topology distributed network control mode based on Fat-Tree gradually reveals its limitations.Software-defined data center network (SDCN) technology, as an improved technology of Fat-Tree network topology, has attracted more and more researchers’ attention.Firstly, an edge computing architecture in SDCN and a task offloading model based on the three-layer service architecture of the mobile edge computing (MEC) platform were built, combined with the actual application scenarios of the MEC platform.Through the same strategy experience playback and entropy regularization, the traditional deep Q-leaning network (DQN) algorithm was improved, and the task offloading strategy of MEC platform was optimized.An improved DQN algorithm based on same strategy empirical playback and entropy regularization (RSS2E-DQN) was compared with three other algorithms in load balancing, energy consumption, delay and network usage.It is verified that the improved algorithm has better performance in the above four aspects.